COMPARISON OF CAPITAL ADEQUACY RATIO IN PT BNI TBK AND PT BRI TBK - Rahayu, Defita; Alwi, Alwi (Jurnal Ekonomi Balance, 2019)
The purpose of this study was to find out how much a significant difference between CAR BNI and BRI. The sampling technique in this study used purposive sampling. This research sample for 5 years from 2014-2018 was listed on the Indonesia Stock Exchange. Types of quantitative research data with secondary data sources. The data analysis technique used independent sample t-test. The analysis shows that the CAR variable on BNI and BRI based on the Sig (2-tailed) value of 0.010 so that a significant value of 0.010 <0, 05, then Ho is rejected and Ha is accepted stating that there is a significant difference between the average CAR on BNI and BRI . Of the two banks, BNI's average is 17.760% smaller than the BRI's average of 21.332%. This shows that during 2014-2018 BRI's CAR was better than BNI, due to the increase in the amount of capital received by BRI. When referring to the minimum Bank Indonesia regulation is 8%, both banks have good financial performance in terms of (CAR).